Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Produk (Study Kasus Pada Mahasiswa FEB UNISMA Konsumen Pesen Kopi Cabang Sigura-gura Malang) - Muchamad Rizal Nurfaizi; Agus Widarko; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThe purpose of this research is to analyze the effect of marketing mix (product, price, promotion, place) on purchasing decisions.This research uses quantitative methods by collecting data through questionnaires. The population in this research were students of FEB UNISMA (Islamic University of Malang). The sampling technique uses purposive sampling with the criteria of FEB UNISMA students (Islamic University of Malang) who have made a purchase at the Malang Pesen Kopi Branch, Sigura-gura Malang. The sample was 91 respondents with a questionnaire collection technique. Technical data analysis in this study uses descriptive analysis techniques and multiple linear regression. The results of this research prove that the first hypothesis tests the relationship of marketing mix (product, price, promotion, place) to the purchase decision simultaneously. The second hypothesis examines the relationship of marketing mix (product, price, promotion, location) partially influential, which results in the product and place having a partially insignificant effect on purchasing decisions. Price and promotion have a partially significant effect on purchasing decisions. Keywords : Marketing mix (product, price, promotion, place), Purchasing decision.